PARINDO EM CASA NO BRASIL: CONSTRUÇÃO DE REDES ENTRE AS EQUIPES DE ATENÇÃO AO PARTO DOMICILIAR PLANEJADO - Pompeu, Kelen da Costa (2019)
Introduction: The current model of childbirth care in Brazil is centered on the hospital and on the doctor. The change of this paradigm has been occurring through the demands of women and the humanizing movement of the delivery and the birth. Planned Home Birth (PDP) came to be seen as an alternative of choosing women to give birth and the family home became a possible scenario for safe births. Currently, there is no data on the number of Brazilian teams of attention to the PDP, in which regions of the country they attend and how they are organized. The absence of these data prevents the systematization of accurate information on this assistance model and makes communication among the teams difficult. General purpose: Map and describe the Planned Home Care Teams in Brazil, with ways to develop a site for the location and the distance communication of these. Methodology: The study contemplates an Integrative Review of Literature for the analysis of the national scientific productions related to PDP in Brazil from 2011 to 2018, by means of a research in the database of the Scientific Electronic Library Online (SciELO) and in the Virtual Health Library (VHL), in which 27 national studies on the topic were discussed. A descriptive observational study of quantitative approach for mapping and describing PDP care teams in Brazil was also carried out. This was done through data collection, by means of an electronic form, through the Snow Ball or Snowball method, which mapped 70 PDP teams in the national territory and described 34 of them. Finally, a free-access site was developed and built for the population. Results: PDP is a modality of health care that composes the network of integral attention to maternal and child health in Brazil. Although this form of assistance is in the process of recognition, expansion and consolidation in the national scenario, its practices will be better structured through studies that first map and describe the organization of the existing teams and the practices already developed to later contribute with proposals that favor the implementation of this new assistance model, based on national and international policies and programs for childbirth care. Final remarks: The researches presented in this dissertation correspond to the authors' research line, which includes topics related to the production of knowledge, technologies and practices that contribute to the structuring, organization, qualification and consolidation of the integral maternal and child health care network. It is hoped that the findings demonstrated here, as well as the product developed, will favor maternal and child health, with care and resolve, aligned with the national and international policies and programs. Also, it is intended to foster entrepreneurial actions in the nursing and health area, in order to transcend the fragmented and linear vision of the organization and management of maternal and child health care and strengthen Public Health Policies. Dissertation Product: There is a product of the dissertation, a website: https://www.nasceremcasabrasil.com.br, being the first virtual space in Brazil to offer an interactive map, with the purpose of offering visibility to the Brazilian PDP care teams, allowing to the population to have the contact of these in their region, as well as the teams have a way to know and to communicate. In addition, the site will also provide scientific evidence on PDP in Brazil and worldwide as well as have access links to relevant scientific articles, which will be updated periodically. It is a product that will be available to class organs, government institutions and the access of the general population through its dissemination in virtual social networks. This unpublished product also aims to collaborate in the orientation of practices and actions of PDP care teams and thus foster strategies for the creation of assistance protocols and on the impact of the Public Policies for the PDP.